The relation of integrated psychological therapy to resting state functional brain connectivity networks in patients with schizophrenia. (December 2021) - Gallos, I.K.; Mantonakis, L.; Spilioti, E.; Kattoulas, E.; Savvidou, E.; Anyfandi, E.; Karavasilis, E.; Kelekis, N.; Smyrnis, N.; Siettos, C.I.
Highlights: Integrated psychological therapy (IPT) of cognitive deficits in patients with schizophrenia. IPT restored to normal the resting state functional brain connectivity of specific networks. These changes remained at one year follow up in IPT treated patients. rsfMRI as a therapeutic monitoring biomarker of cognitive remediation therapy in schizophrenia. Abstract: Functional brain dysconnectivity measured with resting state functional magnetic resonance imaging (rsfMRI) has been linked to cognitive impairment in schizophrenia. This study investigated the effects on functional brain connectivity of Integrated Psychological Therapy (IPT), a cognitive behavioral oriented group intervention program, in 31 patients with schizophrenia. Patients received IPT or an equal intensity non-specific psychological treatment in a non-randomized design. Evidence of improvement in executive and social functions, psychopathology and overall level of functioning was observed after treatment completion at six months only in the IPT treatment group and was partially sustained at one-year follow up. Independent Component Analysis and Isometric Mapping (ISOMAP), a non-linear manifold learning algorithm, were used to construct functional connectivity networks from the rsfMRI data. Functional brain dysconnectivity was observed in patients compared to a group of 17 healthy controls, both globally and specifically including the default mode (DMN) and frontoparietal network (FPN). DMN and FPN connectivity were reversed towards healthy control patterns only in the IPT treatment group and these effects were sustained at follow up for DMN but not FPN. These data suggest the use of rsfMRI as a biomarker for accessing and monitoring the therapeutic effects of cognitive remediation therapy in schizophrenia.